PENELITIAN TINDAKAN KELAS DALAM MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK PENINGKATAN HASIL BELAJAR IPS DI SMPII LUQMAN AL-HAKIM BATAM - Enik Nurfaizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve social studies learning outcomes through the problem based learning model for class VIII students of SMPII Luqman Al-Hakim Batam in the academic year 2024-2025. The subjects of this classroom action research were 38 class VIII students of SMP SMPII Luqman Al-Hakim Batam as the subjects receiving the action, while the subjects doing the action were the class VIII B social studies teacher as the teacher, colleagues as the subjects who observed the learning process, and the Principal as the subject of the data source. The data collection method was carried out through test, observation and documentation techniques. This action research was carried out in two cycles, each cycle consisting of: planning, action, observation and reflection. The results of this study indicate that the use of the problem based learning model can improve social studies learning outcomes for class VIII students of SMP SMPII Luqman Al-Hakim Batam in the academic year 2024-2025. This can be seen from the average value of students' social studies learning outcomes also increased, namely before the action of 70.88 in cycle I of 74.80 and in cycle II of 85.37. In addition, the percentage of student learning completion, namely before the action of 34.28%, in cycle I of 74.80% and in cycle II of 94.28%.